Pengaruh L-Sistein terhadap Efisiensi Transformasi Genetik Jagung (Zea mays) Menggunakan Agrobacterium - Setyo Dwi Utomo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
An efficient procedure of genetic transformation ultimately can accelerate the process of cultivar development of maize.  The objective of this study was to evaluate the effect of L-cysteine added to co-cultivation medium on the efficiency of Agrobacterium-mediated transformation of two genotypes of maize.  Explants of immature embryos were isolated from immature ears genotypes Hi-II and Tom Thumb harvested 11-13 days after pollination.  Then explants were inoculated with Agrobacterium strain C58C1 carrying pPTN345 vector and cultured in co-cultivation medium for 2 days then on delay medium for 14 days, on selection medium for 4 x 14 days, on regeneration medium, and finally on germination medium.  Co-cultivation media contained either 0 or 100 mg/L L-cysteine.  Based on assay at 2 days after inoculation,the transient expression of GUS at scutelar side of explants co-cultivated on medium containing 100 mg/L cysteine was higher than that of the control (0 mg/L cysteine).  Transient expression of GUS on the explants of Tom Thumb was higher than that of Hi-II.  However, transgenic plants in this study were only produced from Hi-II explants co-cultivated in a medium amended with 100 mg/L L-cysteine. No transgenic plants was produced from explants of Tom Thumb due to low efficiency of induction of embriogenic calli.  The efficiency of transformation using explants of Hi-II cocultivated in a medium amended with 100 mg/L L-cysteine was 4 independent transformants or transgenic plants out of 70 explants inoculated or 5.7%.    Key words:  Agrobacterium tumefaciens, corn, L-cysteine, Hi-II, Tom Thumb